High-flowability heavy calcium carbonate for hard PVC (polyvinyl chloride) as well as preparation method and application of high-flowability heavy calcium carbonate

Through the modification technology, ultrafine heavy calcium carbonate is combined with light calcium carbonate and modifier to prepare high-flow heavy calcium carbonate, which solves the problem of poor processing fluidity of heavy calcium carbonate in hard PVC, and achieves better plasticization effect and production continuity.

CN119859320APending Publication Date: 2025-04-22LIANZHOU GUANGYUAN CALCIUM CARBONATE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510150061.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The poor processing fluidity of heavy calcium carbonate in hard PVC leads to poor plasticization effect and discontinuous production, making it difficult to meet the needs of industrial applications.

Method used

High-flow heavy calcium carbonate was prepared by mixing and modifying ultrafine heavy calcium carbonate with long carbon chain stearic acid, then kneading and modifying with light calcium carbonate, and finally compounding with ethylene bisstearic acid amide and metal soap lubricant.

Benefits of technology

The processing fluidity of heavy calcium carbonate is improved, its plasticization effect in hard PVC is enhanced, the problem of poor processing fluidity is solved, and the production continuity and output are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005267794110000121
    Figure BDA0005267794110000121
  • Figure BDA0005267794110000122
    Figure BDA0005267794110000122
  • Figure BDA0005267794110000131
    Figure BDA0005267794110000131
Patent Text Reader

Abstract

The invention provides high-flowability heavy calcium carbonate for hard PVC (polyvinyl chloride) as well as a preparation method and application of the high-flowability heavy calcium carbonate, and belongs to the technical field of functional inorganic non-metallic materials. The preparation method comprises the following steps: blending and modifying superfine heavy calcium carbonate with stearic acid, kneading and blending with light calcium carbonate, and carrying out composite modification by adopting a composite modifier to obtain the high-fluidity heavy calcium carbonate for the hard PVC. By adopting a light-heavy composite modification technology, the particle size distribution of the heavy calcium carbonate is uniform, the processing fluidity is improved, and the problem that the processing fluidity is poor when high-filling heavy calcium carbonate is added in the hard PVC industry is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional inorganic non-metallic materials, and in particular to high-fluidity heavy calcium carbonate for rigid PVC, and a preparation method and application thereof. Background Art

[0002] PVC (polyvinyl chloride plastic) is a common plastic material in daily life. According to different manufacturing methods and processing conditions, PVC can be divided into two types: hard PVC and soft PVC. Hard PVC has high hardness, excellent heat resistance, electrical insulation and chemical corrosion resistance, etc. It is widely used in building materials, industrial products, plastic pipes, doors and windows, panels and other industries.

[0003] Heavy calcium carbonate is an inorganic powder prepared by physical grinding of natural calcium carbonate salt ores such as calcite, marble, and dolomite. It is often used as a filler for rigid PVC due to its low price, high chemical purity, high inertness, good thermal stability, non-toxicity, tastelessness, and odorlessness. It is also the largest inorganic filler added to rigid PVC. With the demand of rigid PVC manufacturers to reduce costs, the amount of heavy calcium carbonate added to rigid PVC has gradually increased. Since the melt viscosity of PVC resin is high, the intermolecular force is strong, and the fluidity is poor during the processing, its processing fluidity will further deteriorate with the increase in the amount of heavy calcium carbonate added; poor processing fluidity will lead to poor plasticization effect and product defects, and poor processing fluidity will also lead to discontinuous production and low output. The factors that affect the processing fluidity of rigid PVC by heavy calcium carbonate include particle size and particle size distribution, surface activation effect, and its dispersibility in PVC resin.

[0004] Light calcium carbonate is a kind of calcium carbonate prepared by chemical processing. It is called light calcium carbonate because its sedimentation volume is larger than that of heavy calcium carbonate produced by grinding. Compared with heavy calcium carbonate, its particle morphology is regular, it is easier to combine with the modifier during surface activation treatment, and the activation efficiency is high; however, light calcium carbonate is more likely to agglomerate, and its processing fluidity is poor when used in hard PVC substrates.

[0005] Therefore, when heavy calcium carbonate or light calcium carbonate is used in the field of rigid PVC, its processing fluidity cannot meet the ideal usage scenario requirements. Summary of the invention

[0006] The purpose of the present invention is to provide a high-fluidity heavy calcium carbonate for rigid PVC, and a preparation method and application thereof. The heavy calcium carbonate is used to compound light calcium carbonate, so as to improve the processing fluidity of the heavy calcium carbonate and meet the application demand for heavy calcium carbonate in the rigid PVC field.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing high-fluidity heavy calcium carbonate for rigid PVC, comprising the following steps:

[0009] The ultrafine heavy calcium carbonate is mixed with a first modifier for blending and modification to obtain modified heavy calcium carbonate; the first modifier is a long carbon chain stearic acid;

[0010] kneading and modifying the modified heavy calcium carbonate and light calcium carbonate to obtain composite calcium carbonate;

[0011] The composite calcium carbonate is mixed with a second modifier to perform composite modification to obtain high-fluidity heavy calcium carbonate for rigid PVC;

[0012] The second modifier is ethylene bis stearic acid amide and a metal soap lubricant.

[0013] Preferably, the fineness of the ultrafine heavy calcium carbonate is D 50 ≤2μm, D 97 ≤5.5μm.

[0014] Preferably, the long carbon chain stearic acid is at least one of stearic acid 1840, stearic acid 1842 and stearic acid 1838, and the mass of the first modifier is 4 to 9‰ of the mass of ultrafine heavy calcium carbonate.

[0015] Preferably, the blending and modification temperature is 110-130° C., the stirring speed is 900-1800 r / min, and the modification time is 20-60 min.

[0016] Preferably, the mass ratio of the modified heavy calcium carbonate to the light calcium carbonate is 6-9:1-4, the sedimentation volume of the light calcium carbonate is ≥2.4 mL / g, and the whiteness is ≥96.

[0017] Preferably, the kneading modification temperature is 70-100° C., the modification time is 10-40 min, and the mixer speed is 250-500 r / min.

[0018] Preferably, the metal soap lubricant is calcium stearate and zinc stearate; the mass of the ethylene bisstearamide is 1-5‰ of the mass of the composite calcium carbonate, the mass of the calcium stearate is 2-6‰ of the mass of the composite calcium carbonate, and the mass of the zinc stearate is 1-5‰ of the mass of the composite calcium carbonate.

[0019] Preferably, the temperature of the composite modification is 60-110° C., the modification time is 10-40 min, and the speed of the mixer is 200-600 r / min.

[0020] The invention provides high-fluidity heavy calcium carbonate for rigid PVC prepared by the preparation method described in the technical scheme.

[0021] The present invention provides application of the high-fluidity heavy calcium carbonate for rigid PVC described in the above technical solution in the field of rigid PVC.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention adopts light-heavy composite modification technology, that is, light calcium carbonate is used to modify heavy calcium carbonate, and the light calcium carbonate particles are evenly filled in the "holes" between the heavy calcium carbonate particles, so as to achieve uniform particle size distribution of the heavy calcium carbonate and improve processing fluidity.

[0024] (2) The present invention coats the surface of heavy calcium carbonate with an organic modifier through blending modification, and then kneads and blends it, so that smaller particles of light calcium carbonate that are not filled in the "holes" of heavy calcium carbonate particles are adsorbed on the surface of heavy calcium carbonate, thereby achieving a more uniform and complete surface morphology of heavy calcium carbonate and improving the plasticizing effect in hard PVC.

[0025] (3) The modifier selected in the blending modification of the present invention is long-chain stearic acid. The longer the carbon chain, the better its stability and the less likely it is to undergo oxidation reaction. Furthermore, by selecting stearic acid with a higher carbon 18 content, the surface of the heavy calcium carbonate is coated with a monomolecular layer of stearic acid, thereby increasing the number of heavy calcium carbonate and adsorbed light calcium carbonate particles, and at the same time, the adsorption force is stronger.

[0026] (4) The composite modification of the present invention uses ethylene bis stearic acid amide (EBS) and metal soap lubricants. EBS is a waxy solid with a hard texture, and can provide external sliding effect in rigid PVC. The metal soap lubricant uses a high-grade fatty acid salt, which can not only play a lubricating role, but also play a stabilizing role.

[0027] (5) Aiming at the problem of poor processing fluidity of adding highly filled heavy calcium carbonate in the rigid PVC industry, the ultrafine heavy calcium carbonate raw powder selected in the present invention is ultrafine calcium carbonate ground by ball milling equipment. The calcium carbonate particles processed by ball milling equipment have more regular and uniform morphology, narrower particle distribution, and better fineness uniformity, thereby promoting its good dispersibility in PVC; further, after surface modification, it has good compatibility with the PVC substrate, thereby improving the processing fluidity of heavy calcium carbonate in rigid PVC.

[0028] (6) The present invention expands the application of heavy calcium carbonate in rigid PVC by optimizing the ratio of the modifier and selecting a modifier suitable for the rigid PVC field. DETAILED DESCRIPTION

[0029] In the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known in the art.

[0030] The present invention provides a method for preparing high-fluidity heavy calcium carbonate for rigid PVC, comprising the following steps:

[0031] The ultrafine heavy calcium carbonate is mixed with a first modifier for blending and modification to obtain modified heavy calcium carbonate; the first modifier is a long carbon chain stearic acid;

[0032] kneading and modifying the modified heavy calcium carbonate and light calcium carbonate to obtain composite calcium carbonate;

[0033] The composite calcium carbonate is mixed with a second modifier to perform composite modification to obtain high-fluidity heavy calcium carbonate for rigid PVC;

[0034] The second modifier is ethylene bis stearic acid amide and a metal soap lubricant.

[0035] The invention mixes ultrafine heavy calcium carbonate with a first modifier to perform blending modification to obtain modified heavy calcium carbonate.

[0036] In the present invention, the fineness of the ultrafine heavy calcium carbonate is preferably D 50 ≤2μm, more preferably 1.8μm, D 97 ≤5.5 μm, more preferably 4.9 μm. The ultrafine heavy calcium carbonate of the present invention is heavy calcium carbonate processed by ball milling. The present invention has no special limitation on the process of ball milling. The ultrafine heavy calcium carbonate can be obtained by ball milling process known in the art.

[0037] Before mixing the ultrafine heavy calcium carbonate with the first modifier, the present invention preferably dries and dehumidifies the ultrafine heavy calcium carbonate, and the drying and dehumidification temperature is preferably 70-110° C., more preferably 80-90° C., the stirring speed is preferably 30-90 r / min, more preferably 50-60 r / min, and the drying time is preferably 10-50 min, more preferably 20-30 min.

[0038] In the present invention, the first modifier is a long-chain stearic acid; the long-chain stearic acid is preferably at least one of stearic acid 1840, stearic acid 1842 and stearic acid 1838. When the long-chain stearic acid is two or more of the above, the present invention has no special limitation on the ratio of different types of long-chain stearic acid, and any ratio is acceptable.

[0039] In the present invention, the mass of the first modifier is preferably 4-9‰ of the mass of the ultrafine heavy calcium carbonate, and more preferably 5-7‰.

[0040] In the present invention, the temperature of the blending modification is preferably 110-130°C, preferably 120-125°C, the stirring speed is preferably 900-1800r / min, preferably 1200-1440r / min, and the modification time is preferably 20-60min, preferably 30-45min. The blending modification is preferably carried out in a high-speed mixer.

[0041] After obtaining the modified heavy calcium carbonate, the present invention kneads and modifies the modified heavy calcium carbonate with light calcium carbonate to obtain composite calcium carbonate.

[0042] In the present invention, the mass ratio of the modified heavy calcium carbonate to the light calcium carbonate is preferably 6-9:1-4, preferably 7-8:2-3; the sedimentation volume of the light calcium carbonate is preferably ≥2.4mL / g, more preferably 2.6mL / g, and the whiteness is ≥96, more preferably 96.7.

[0043] In the present invention, the kneading modification temperature is preferably 70-100°C, preferably 80-90°C; the modification time is preferably 10-40 min, preferably 20-30 min; the stirrer speed is preferably 250-500 r / min, preferably 350-400 r / min.

[0044] After obtaining the composite calcium carbonate, the present invention mixes the composite calcium carbonate with a second modifier to perform composite modification to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0045] In the present invention, the second modifier is ethylene bisstearic acid amide and a metal soap lubricant.

[0046] In the present invention, the metal soap lubricant is preferably calcium stearate and zinc stearate; the mass of the ethylene bisstearic acid amide is preferably 1-5‰ of the mass of the composite calcium carbonate, preferably 2-3‰; the mass of the calcium stearate is preferably 2-6‰ of the mass of the composite calcium carbonate, preferably 3-4‰; the mass of the zinc stearate is preferably 1-5‰ of the mass of the composite calcium carbonate, preferably 3-4‰.

[0047] In the present invention, the temperature of the composite modification is preferably 60-110°C, more preferably 90-100°C; the modification time is preferably 10-40 min, preferably 20-30 min; the stirrer speed is preferably 200-600 r / min, preferably 300-400 r / min.

[0048] The invention provides high-fluidity heavy calcium carbonate for rigid PVC prepared by the preparation method described in the technical scheme.

[0049] The present invention provides the application of the high-fluidity heavy calcium carbonate for rigid PVC described in the above technical solution in the field of rigid PVC. The present invention has no special limitation on the application method, and the application can be carried out according to the method well known in the art.

[0050] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0051] The following experimental methods and detection methods, unless otherwise specified, are conventional methods; the following reagents and raw materials, unless otherwise specified, are commercially available.

[0052] Example 1

[0053] Weigh 600kg fineness D 50 1.8μm, D 97 The ultra-fine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min.

[0054] The dried powder was transported to a high-speed mixer for surface modification, and 7‰ of stearic acid 1840 relative to the mass of the ultrafine heavy calcium carbonate powder was added for blending modification. The modification temperature was 120°C, the modification time was 45min, and the rotation speed was 1440r / min to obtain modified heavy calcium carbonate.

[0055] 600 kg of modified heavy calcium carbonate after blending and modification was transported to a kneader for kneading and modification, and 400 kg of light calcium carbonate with a sedimentation volume of 2.6 mL / g and a whiteness of 96.7 was added for blending. The kneading temperature was 90° C., the modification time was 20 min, and the kneader speed was 350 r / min to obtain composite calcium carbonate;

[0056] The kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification. Relative to the mass of the composite calcium carbonate, 3‰ ethylene bisstearamide, 4‰ calcium stearate and 3‰ zinc stearate are added for composite modification. The modification temperature is 90°C, the modification time is 30min, and the rotation speed is 400r / min. The composite modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0057] Example 2

[0058] Weigh 700kg fineness D 50 1.8μm, D97 The ultra-fine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min.

[0059] The dried powder was transported to a high-speed mixer for surface modification, and 7‰ of stearic acid 1840 relative to the mass of the ultrafine heavy calcium carbonate powder was added for blending modification. The modification temperature was 120°C, the modification time was 45min, and the rotation speed was 1440r / min to obtain modified heavy calcium carbonate.

[0060] 700 kg of modified heavy calcium carbonate after blending and modification was transported to a kneader for kneading and modification, and 300 kg of light calcium carbonate with a sedimentation volume of 2.6 mL / g and a whiteness of 96.7 was added for blending. The kneading temperature was 90° C., the modification time was 20 min, and the kneader speed was 350 r / min to obtain composite calcium carbonate;

[0061] The kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification. Relative to the mass of the composite calcium carbonate, 3‰ ethylene bisstearamide, 4‰ calcium stearate and 3‰ zinc stearate are added for composite modification. The modification temperature is 90°C, the modification time is 30min, and the rotation speed is 400r / min. The composite modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0062] Example 3

[0063] Weigh 800kg fineness D 50 1.8μm, D 97 The ultra-fine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min.

[0064] The dried powder was transported to a high-speed mixer for surface modification, and 7‰ of stearic acid 1840 relative to the mass of the ultrafine heavy calcium carbonate powder was added for blending modification. The modification temperature was 120°C, the modification time was 45min, and the rotation speed was 1440r / min to obtain modified heavy calcium carbonate.

[0065] 800 kg of modified heavy calcium carbonate after blending and modification was transported to a kneader for kneading and modification, and 200 kg of light calcium carbonate with a sedimentation volume of 2.6 mL / g and a whiteness of 96.7 was added for blending. The kneading temperature was 90° C., the modification time was 20 min, and the kneader speed was 350 r / min to obtain composite calcium carbonate;

[0066] The kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification. Relative to the mass of the composite calcium carbonate, 3‰ ethylene bisstearamide, 4‰ calcium stearate and 3‰ zinc stearate are added for composite modification. The modification temperature is 90°C, the modification time is 30min, and the rotation speed is 400r / min. The composite modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0067] Example 4

[0068] Weigh 900kg fineness D 50 1.8μm, D 97 The ultra-fine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min.

[0069] The dried powder was transported to a high-speed mixer for surface modification, and 7‰ of stearic acid 1840 relative to the mass of the ultrafine heavy calcium carbonate powder was added for blending modification. The modification temperature was 120°C, the modification time was 45min, and the rotation speed was 1440r / min to obtain modified heavy calcium carbonate.

[0070] 900 kg of modified heavy calcium carbonate after blending and modification was transported to a kneader for kneading and modification, and 100 kg of light calcium carbonate with a sedimentation volume of 2.6 mL / g and a whiteness of 96.7 was added for blending. The kneading temperature was 90° C., the modification time was 20 min, and the kneader speed was 350 r / min to obtain composite calcium carbonate;

[0071] The kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification. Relative to the mass of the composite calcium carbonate, 3‰ ethylene bisstearamide, 4‰ calcium stearate and 3‰ zinc stearate are added for composite modification. The modification temperature is 90°C, the modification time is 30min, and the rotation speed is 400r / min. The composite modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0072] Example 5

[0073] Weigh 800kg fineness D 50 1.8μm, D 97 The ultra-fine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min.

[0074] The dried powder was transported to a high-speed mixer for surface modification, and 3‰ of stearic acid 1840 and 4‰ of stearic acid 1842 were added relative to the mass of the ultrafine heavy calcium carbonate powder for blending modification. The modification temperature was 120°C, the modification time was 45min, and the rotation speed was 1440r / min to obtain modified heavy calcium carbonate.

[0075] 800 kg of modified heavy calcium carbonate after blending and modification was transported to a kneader for kneading and modification, and 200 kg of light calcium carbonate with a sedimentation volume of 2.6 mL / g and a whiteness of 96.7 was added for blending. The kneading temperature was 90° C., the modification time was 20 min, and the kneader speed was 350 r / min to obtain composite calcium carbonate;

[0076] The kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification. Relative to the mass of the composite calcium carbonate, 3‰ ethylene bisstearamide, 4‰ calcium stearate and 3‰ zinc stearate are added for composite modification. The modification temperature is 90°C, the modification time is 30min, and the rotation speed is 400r / min. The composite modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0077] Example 6

[0078] Weigh 800kg fineness D 50 1.8μm, D 97 The ultra-fine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min.

[0079] The dried powder was transported to a high-speed mixer for surface modification, and 3‰ of stearic acid 1840 and 4‰ of stearic acid 1838 were added relative to the mass of the ultrafine heavy calcium carbonate powder for blending modification. The modification temperature was 120°C, the modification time was 45min, and the rotation speed was 1440r / min to obtain modified heavy calcium carbonate.

[0080] 800 kg of modified heavy calcium carbonate after blending and modification was transported to a kneader for kneading and modification, and 200 kg of light calcium carbonate with a sedimentation volume of 2.6 mL / g and a whiteness of 96.7 was added for blending. The kneading temperature was 90° C., the modification time was 20 min, and the kneader speed was 350 r / min to obtain composite calcium carbonate;

[0081] The kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification. Relative to the mass of the composite calcium carbonate, 3‰ ethylene bisstearamide, 3‰ calcium stearate and 3‰ zinc stearate are added for composite modification. The modification temperature is 90°C, the modification time is 30min, and the rotation speed is 400r / min. The composite modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0082] Example 7

[0083] Weigh 800kg fineness D 50 1.8μm, D 97 The ultra-fine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min.

[0084] The dried powder was transported to a high-speed mixer for surface modification, and 3‰ of stearic acid 1842 and 4‰ of stearic acid 1838 were added relative to the mass of the ultrafine heavy calcium carbonate powder for blending modification. The modification temperature was 120°C, the modification time was 45min, and the rotation speed was 1440r / min to obtain modified heavy calcium carbonate.

[0085] 800 kg of modified heavy calcium carbonate after blending and modification was transported to a kneader for kneading and modification, and 200 kg of light calcium carbonate with a sedimentation volume of 2.6 ml / g and a whiteness of 96.7 was added for blending. The kneading temperature was 90° C., the modification time was 20 min, and the kneader speed was 350 r / min to obtain composite calcium carbonate;

[0086] The kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification. Relative to the mass of the composite calcium carbonate, 2‰ ethylene bisstearamide, 4‰ calcium stearate and 4‰ zinc stearate are added for composite modification. The modification temperature is 90°C, the modification time is 30min, and the rotation speed is 400r / min. The composite modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0087] Comparative Example 1

[0088] The ultrafine heavy calcium carbonate GY-716 produced by Lianzhou Guangyuan Calcium Carbonate Co., Ltd. is used as comparative example 1.

[0089] Comparative Example 2

[0090] Light calcium carbonate produced by Lianzhou Yufeng Calcium Technology Co., Ltd. is used as Comparative Example 2.

[0091] Comparative Example 3

[0092] Weigh 800kg fineness D50 1.8μm, D 97 The ultrafine heavy calcium carbonate powder with a diameter of 4.9 μm is transported to a vertical dryer for drying and dehumidification, with a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min; the dried powder is transported to a high-speed mixer for surface modification, and stearic acid 1801 with a mass of 7‰ relative to the ultrafine heavy calcium carbonate powder is added for blending modification, with a modification temperature of 120°C, a modification time of 45 min, and a rotation speed of 1440 r / min; the blended and modified heavy calcium carbonate is transported to a kneader for kneading modification, and 200 kg of sedimentation volume 2.6 mL / g is added, The light calcium carbonate with a whiteness of 96.7 is blended, the kneading temperature is 90°C, the modification time is 20min, and the kneading machine speed is 350r / min; the kneaded modified composite calcium carbonate is conveyed to a low-speed modifier for composite modification, and relative to the mass of the composite calcium carbonate, 3‰ ethylene bisstearamide, 4‰ calcium stearate, and 3‰ zinc stearate are added for composite modification, the modification temperature is 90°C, the modification time is 30min, and the speed is 400r / min; the heavy calcium carbonate after the composite modification is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0093] Comparative Example 4

[0094] Weigh 800kg fineness D 50 1.8μm, D 97 The ultrafine heavy calcium carbonate powder with a size of 4.9 μm was transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min; the dried powder was transported to a high-speed mixer for surface modification, and 3‰ of stearic acid 1840 and 4‰ of stearic acid 1842 were added relative to the mass of the ultrafine heavy calcium carbonate powder for blending modification at a modification temperature of 120°C, a modification time of 45 min, and a rotation speed of 1440 r / min; the blended and modified heavy calcium carbonate was transported to a kneader for kneading modification, and 200 The composite calcium carbonate having a sedimentation volume of 2.6 mL / g and a whiteness of 96.7 is blended, the kneading temperature is 90°C, the modification time is 20 min, and the kneading machine speed is 350 r / min; the kneaded and modified composite calcium carbonate is conveyed to a low-speed modifier for surface modification, and 10‰ ethylene bisstearic acid amide is added relative to the mass of the composite calcium carbonate for modification, the modification temperature is 90°C, the modification time is 30 min, and the speed is 400 r / min; the modified heavy calcium carbonate is conveyed to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0095] Comparative Example 5

[0096] Weigh 800kg fineness D 501.8μm, D 97 The ultrafine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification at a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min; the dried powder is transported to a high-speed mixer for surface modification, and 3‰ of stearic acid 1840 and 4‰ of stearic acid 1842 are added relative to the mass of the ultrafine heavy calcium carbonate powder for modification. The modification temperature is 120°C, the modification time is 45 min, and the rotation speed is 1440 r / min; the high-mix modified heavy calcium carbonate is transported to a kneader for kneading modification, and the addition 200 kg of light calcium carbonate with a sedimentation volume of 2.6 ml / g and a whiteness of 96.7 was added for blending, the kneading temperature was 90°C, the modification time was 20 min, and the kneading machine speed was 350 r / min; the kneaded and modified composite calcium carbonate was transported to a low-speed modifier for modification, relative to the composite calcium carbonate, 10‰ calcium stearate was added for modification, the modification temperature was 90°C, the modification time was 30 min, and the speed was 400 r / min; the modified heavy calcium carbonate was transported to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0097] Comparative Example 6

[0098] Weigh 800kg fineness D 50 1.8μm, D 97 The ultrafine heavy calcium carbonate powder with a size of 4.9 μm is transported to a vertical dryer for drying and dehumidification, with a drying temperature of 90°C, a stirring speed of 60 r / min, and a drying time of 30 min; the dried powder is transported to a high-speed mixer for surface modification, and 3‰ of stearic acid 1840 and 4‰ of stearic acid 1842 relative to the mass of the ultrafine heavy calcium carbonate powder are added for modification, the modification temperature is 120°C, the modification time is 45 min, and the rotation speed is 1440 r / min; the high-mix modified heavy calcium carbonate is transported to a kneader for kneading and modification, and added 200kg of light calcium carbonate with a sedimentation volume of 2.6mL / g and a whiteness of 96.7 is blended, the kneading temperature is 90°C, the modification time is 20min, and the kneading machine speed is 350r / min; the kneaded modified composite calcium carbonate is transported to a low-speed modifier for modification, and 10‰ zinc stearate is added relative to the mass of the composite calcium carbonate for modification, the modification temperature is 90°C, the modification time is 30min, and the speed is 400r / min; the modified heavy calcium carbonate is transported to a cooler and cooled to room temperature to obtain high-fluidity heavy calcium carbonate for rigid PVC.

[0099] Performance Testing

[0100] The performance tests were performed on the products in Examples 1 to 7 and Comparative Examples 1 to 6:

[0101] 1. The specific test of oil absorption value is:

[0102] Weigh 5 g of the product (accurate to 0.01) and place it on a glass plate. Stir the product evenly with a spatula while adding dioctyl phthalate (DOP) dropwise. Stir continuously until the added DOP completely bonds the products together, i.e., reaches saturation. Record the volume of DOP consumed.

[0103] Oil absorption = v / m × 100

[0104] m: weight of the product (in g);

[0105] v: volume of DOP consumed (in mL);

[0106] The unit of oil absorption is mL / 100g.

[0107] 2. The specific test of activation degree is:

[0108] Weigh 5 g of the product (accurate to 0.01 g) and place it in a separatory funnel. Add 200 mL of water and shake it back and forth at a speed of 120 times / min for 1 min. Place it gently on the funnel stand and let it stand for 30 min until obvious stratification occurs. Then put the precipitated calcium carbonate into a glass sand crucible that has been dried to a constant mass at 105°C in advance. Filter out the water, place the filter residue in an electric constant temperature drying oven at 105°C and dry it to a constant mass, and calculate the degree of activation.

[0109] The activation degree is expressed as mass fraction ω, and the value is expressed as %, and is calculated according to the following formula:

[0110]

[0111] in:

[0112] ω is the degree of activation (in %);

[0113] m2 is the weight of the crucible and the sunken calcium carbonate after drying (in g);

[0114] m1 is the weight of the crucible (in g);

[0115] m is the weight of the sample (in g).

[0116] 3. The particle size test was carried out using the BT-9300ST laser particle size analyzer produced by Liaoning Dandong Better Co., Ltd. 50 Represents the particle size value corresponding to 50% of the cumulative distribution; D 97 It represents the particle size value corresponding to 97% of the cumulative distribution.

[0117] The results are shown in Table 1.

[0118] Table 1 Comparison of particle size distribution, oil absorption value and activation index of the products in Examples 1 to 7 and Comparative Examples 1 to 6

[0119]

[0120]

[0121] From the results in Table 1, it can be seen that the oil absorption value of GY-716 (Comparative Example 1) is 30 mL / 100 g, and the oil absorption value of light calcium carbonate (Comparative Example 2) is 36 mL / 100 g; after adopting the modification process of the present invention (Examples 1-7), the oil absorption value is reduced to ≤22 mL / 100 g, and the activation degree is ≥95%, indicating that the surface modification treatment of heavy calcium carbonate is achieved by adopting the process of the present invention. Heavy calcium carbonate with low oil absorption value and high activation degree is applied to the field of rigid PVC, and its processing fluidity will be better.

[0122] In the research on optimizing the surface modification additive, compared with comparative example 3, stearic acid 1801 is used, and its oil absorption value is 24mL / 100g, and its activation degree is 84.5%; the higher the content of stearic acid C18, the better the effect of modifying heavy calcium carbonate. In the selection of composite modification additives, comparative example 4 uses a single ethylene bis stearic acid amide, and its oil absorption value is 26mL / 100g, and its activation degree is 80.2%; comparative example 5 uses a single calcium stearate, and its oil absorption value is 28mL / 100g, and its activation degree is 83.5%; comparative example 6 uses a single zinc stearate, and its oil absorption value is 28mL / 100g, and its activation degree is 84.6%; compared with the comparative examples, the stearic acid model and the selection of composite modification additives used in Examples 1 to 7 have obvious modification effects.

[0123] From the above results, it can be found that it is feasible to modify ultrafine heavy calcium carbonate using the modification process of the present invention. At the same time, it can be predicted that the heavy calcium carbonate prepared by the present invention will have a better application effect in rigid PVC.

[0124] Application effect evaluation

[0125] In order to verify the application effect of the heavy calcium carbonate prepared by the present invention in rigid PVC, the heavy calcium carbonate prepared in Example 5 and Comparative Examples 1 to 6 were selected and weighed according to the following formula for raw material preparation. After being fully mixed, the raw materials were extruded on a single screw extruder to form a sheet, and its processing flowability was examined.

[0126] Experimental raw materials and formula: 150 parts of PVC resin (SG-5), Cangzhou Julong Chemical Co., Ltd.; 225 parts of calcium carbonate filler (Example 5 and Comparative Examples 1 to 6); 15 parts of composite stabilizer HS-00, Dongguan Weisheng Plastic Technology Co., Ltd.; 1.5 parts of semi-refined paraffin, China National Petroleum Corporation.

[0127] Related reviews:

[0128] Processing current: observe the processing current meter on the host control panel;

[0129] Extrusion processability: observe the discharge of the die head sheet material;

[0130] The results are shown in Table 2.

[0131] Table 2 Processing properties of PVC gussets prepared from heavy calcium carbonate in Example 5 and Comparative Examples 1 to 6

[0132] Filler Type Processing current (A) Extrusion processability Example 5 25 Very easy to extrude, very good processing fluidity Comparative Example 1 35 Difficult to process, high melt pressure, poor fluidity Comparative Example 2 46 Very difficult to process, poor fluidity Comparative Example 3 28 The processing fluidity is average, and the board output speed is slightly slow Comparative Example 4 29 The processing fluidity is average, and the board output speed is slightly slow Comparative Example 5 30 Poor processing fluidity and slow board output speed Comparative Example 6 29 Poor processing fluidity and slow board output speed

[0133] It can be seen from the results in Table 2 that the heavy calcium carbonate of the present invention has a small processing current and good extrusion processing performance in the preparation process of PVC gusset plate. Compared with unmodified heavy calcium carbonate (Comparative Example 1) and light calcium carbonate (Comparative Example 2), the heavy calcium carbonate prepared by the present invention significantly improves its processing fluidity; compared with Comparative Examples 3 to 6 without optimized modification additives, it has good processing fluidity and fast plate extrusion speed.

[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing high-fluidity heavy calcium carbonate for rigid PVC, characterized in that: The following steps are involved: Mixing ultrafine heavy calcium carbonate with a first modifier to perform blending modification to obtain modified heavy calcium carbonate; The first modifier is long carbon chain stearic acid; kneading and modifying the modified heavy calcium carbonate and light calcium carbonate to obtain composite calcium carbonate; The composite calcium carbonate is mixed with a second modifier to perform composite modification to obtain high-fluidity heavy calcium carbonate for rigid PVC; The second modifier is ethylene bis stearic acid amide and a metal soap lubricant.

2. The preparation method according to claim 1, characterized in that: The fineness of the ultrafine heavy calcium carbonate is D 50 ≤2μm, D 97 ≤5.5μm.

3. The preparation method according to claim 1 or 2, characterized in that: The long carbon chain stearic acid is at least one of stearic acid 1840, stearic acid 1842 and stearic acid 1838, and the mass of the first modifier is 4-9‰ of the mass of ultrafine heavy calcium carbonate.

4. The preparation method according to claim 3, characterized in that: The temperature of the blending modification is 110-130° C., the stirring speed is 900-1800 r / min, and the modification time is 20-60 min.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the modified heavy calcium carbonate to the light calcium carbonate is 6-9:1-4, the sedimentation volume of the light calcium carbonate is ≥2.4 mL / g, and the whiteness is ≥96.

6. The preparation method according to claim 1 or 5, characterized in that: The kneading modification temperature is 70-100° C., the modification time is 10-40 min, and the stirring speed is 250-500 r / min.

7. The preparation method according to claim 1, characterized in that: The metal soap lubricant is calcium stearate and zinc stearate; the mass of the ethylene bis stearic acid amide is 1-5‰ of the mass of the composite calcium carbonate, the mass of the calcium stearate is 2-6‰ of the mass of the composite calcium carbonate, and the mass of the zinc stearate is 1-5‰ of the mass of the composite calcium carbonate.

8. The preparation method according to claim 1 or 7, characterized in that: The temperature of the composite modification is 60-110° C., the modification time is 10-40 minutes, and the speed of the mixer is 200-600 r / min.

9. High-fluidity heavy calcium carbonate for rigid PVC prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the high-fluidity heavy calcium carbonate for rigid PVC according to claim 9 in the field of rigid PVC.